The Effect of Motivation and Learning Style on Students' Mathematics Learning Achievement - Samuel Juliardi Sinaga (Universitas Pahlawan Tuanku Tambusai, 2022)
Based on field observations that I did on learning Mathematics at SMA Negeri 3 Pematangsiantar, there are still many students whose learning responses are still lacking and students do not do assignments and when asked why they don't do their assignments they have many reasons. This study aims to determine the effect of motivation on students' mathematics learning achievement, the effect of learning styles on mathematics learning achievement and the influence of motivation and learning styles on students' mathematics learning achievement. In this study, the researcher used quantitative research methods. The quantitative method is a positivistic method because it is based on the philosophy of positivism. This method is a scientific method because it has fulfilled scientific principles, namely concrete/empirical, objective, measurable, rational, and systematic. The population in this study were students of class XI SMA Negeri 3 Pematangsiantar totaling 290 students. The results of the research and discussion have a positive influence between motivation and learning style on students' mathematics learning achievement. Based on the results of the research and discussion, it can be concluded that there is a positive and significant influence between motivation on learning achievement in mathematics for class XI students at SMA Negeri 3 Pematangsiantar.